Nanostructured Polymeric Functional Micelles for Drug Delivery Applications. Issue 1 (December 2013) - Tripodo, G.; Mandracchia, D.; Dorati, R.; Latrofa, A.; Genta, I.; Conti, B.; Lendlein, Andreas; Neffe, Axel T.
Summary Inulin (INU) is a polyfructose which have the unique features to not bind plasmatic proteins and to be totally filtered by the kidneys where it is neither secreted nor reabsorbed. These behaviors make it an ideal candidate to target and delivery drugs into the kidneys for the therapy of urinary tract affections. On the other side, Vitamin E (VITE) is a hydrophobic molecule with important antioxidant activities. Therefore, the chemical conjugation of INU and VITE, led to amphiphilic INVITE polymers able to self‐assemble in nanostructured micelle. The obtained micelle have been drug loaded with the model hydrophobic drug curcumin (solubility ≈ 11 ng/ml), the drug release and micelles stability studies have been performed in‐vitro in simulated physiological fluids. Furthermore, biological studies on suitable cell lines have been carried out to assess the cytotoxicity of INVITE conjugates.